Detection of residual disease in chronic myeloid leukemia utilizing genomic next generation sequencing reveals persistence of differentiated Ph+ B cells but not bone marrow stem/progenitors. Issue 3 (23rd February 2021) - Karigane, Daiki; Kasahara, Hidenori; Shiroshita, Kouhei; Fujita, Shinya; Kobayashi, Hiroshi; Tamaki, Shinpei; Yamazaki, Rie; Yahagi, Kaori; Yatabe, Yoko; Kondoh, Naomi; Arai, Tomoko; Katagiri, Hisako; et al.
Abstract: Persistence of leukemic stem cells (LSCs) results in the recurrence of chronic myeloid leukemia (CML) after the administration of tyrosine kinase inhibitors (TKIs). Thus, the detection of minimal residual disease (MRD) with LSC potential can improve prognosis. Here, we analyzed 115 CML patients and found that CD25 was preferentially expressed on the phenotypic stem and progenitor cells (SPCs), and TKI therapy decreased the number of CD25-positive cells in the SPC fraction. To detect MRD harboring BCR-ABL1 fusion DNA, we developed a highly-sensitive method using patient-specific primers and next-generation sequencing. By using this method, we identified that in patients who achieved molecular remission, almost all residual CD25-positive SPCs were BCR-ABL1 -negative. Moreover, in some patients BCR-ABL1 was detectable in peripheral B cells but not in SPCs. We conclude that CD25 marks LSCs at diagnosis but does not mark MRD following TKI treatment and that analysis of peripheral B cells can allow sensitive detection of MRD.